Protein kinetics of superoxide dismutase‐1 in familial and sporadic amyotrophic lateral sclerosis - Cindy V. Ly; Margaret D. Ireland; Wade K. Self; James Bollinger; Jennifer Jockel‐Balsarotti; Hillary Herzog; Peggy Allred; Leah Miller; Michael Doyle; Isabel Anez‐Bruzual; Bhavesh Trikamji; Ted Hyman; et al. (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective Accumulation of misfolded superoxide dismutase‐1 (SOD1) is a pathological hallmark of SOD1‐related amyotrophic lateral sclerosis (ALS) and is observed in sporadic ALS where its role in pathogenesis is controversial. Understanding in vivo protein kinetics may clarify how SOD1 influences neurodegeneration and inform optimal dosing for therapies that lower SOD1 transcripts. Methods We employed stable isotope labeling paired with mass spectrometry to evaluate in vivo protein kinetics and concentration of soluble SOD1 in cerebrospinal fluid (CSF) of SOD1 mutation carriers, sporadic ALS participants and controls. A deaminated SOD1 peptide, SDGPVKV, that correlates with protein stability was also measured. Results In participants with heterozygous SOD1A5V mutations, known to cause rapidly progressive ALS, mutant SOD1 protein exhibited ~twofold faster turnover and ~ 16‐fold lower concentration compared to wild‐type SOD1 protein. SDGPVKV levels were increased in SOD1A5V carriers relative to controls. Thus, SOD1 mutations impact protein kinetics and stability. We applied this approach to sporadic ALS participants and found that SOD1 turnover, concentration, and SDGPVKV levels are not significantly different compared to controls. Interpretation These results highlight the ability of stable isotope labeling approaches and peptide deamidation to discern the influence of disease mutations on protein kinetics and stability and support implementation of this method to optimize clinical trial design of gene and molecular therapies for neurological disorders. Trial Registration Clinicaltrials.gov: NCT03449212.